2015
DOI: 10.1002/pmic.201400304
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine enema regulates colonic ubiquitinated proteins but not proteasome activities during TNBS‐induced colitis leading to increased mitochondrial activity

Abstract: Ubiquitin proteasome system contributes to the regulation of intestinal inflammatory response as its inhibition is associated with tissue damage improvement. We aimed to evaluate whether glutamine is able to limit inflammation by targeting ubiquitin proteasome system in experimental colitis. Colitis was induced in male rats by intrarectal instillation of 2-4-6-trinitrobenzen sulfonic acid (TNBS) at day 1. From day 2 to day 6, rats daily received either an intrarectal instillation of PBS (TNBS/PBS group) or glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Moreover, elevated levels of PKM2 were found in stool samples from patients with active Crohn’s disease, suggesting that this protein can be a useful non-invasive marker for inflammatory bowel disease ( 63 , 64 ). In accordance with this, expression of PKM2 was progressively increased in intestinal tissue of mice undergoing TNBS-induced colitis ( 62 , 65 ). Finally, proteomic analysis revealed that PKM2 was one of the 33 over-expressed proteins found in synovial tissue from patients with rheumatoid arthritis ( 66 ).…”
Section: Pkm2 As a New Player In Inflammationsupporting
confidence: 66%
“…Moreover, elevated levels of PKM2 were found in stool samples from patients with active Crohn’s disease, suggesting that this protein can be a useful non-invasive marker for inflammatory bowel disease ( 63 , 64 ). In accordance with this, expression of PKM2 was progressively increased in intestinal tissue of mice undergoing TNBS-induced colitis ( 62 , 65 ). Finally, proteomic analysis revealed that PKM2 was one of the 33 over-expressed proteins found in synovial tissue from patients with rheumatoid arthritis ( 66 ).…”
Section: Pkm2 As a New Player In Inflammationsupporting
confidence: 66%
“…Similarly to previous studies[13-15,17-20], we observed colon inflammation demonstrated by stiffened colon, histological inflammatory score or increased inflammatory markers. We also noted SPECT signs of inflammation such as an increased maximal thickness of colon.…”
Section: Discussionsupporting
confidence: 88%
“…By using a rectal route or targeted delivery of glutamine, high concentrations of glutamine can be easily achieved in the colonic lumen. Even if luminal amino acids are not considered to be able to enter the colonocytes, 25 , 26 previous data reported reduced colonic inflammatory response after a rectal supply of glutamine in both animals 27 , 28 and humans 29 . More interestingly, we observed that the effects of glutamine depended on the basal expression of claudin‐1, suggesting that the lower the basal claudin‐1 expression, the greater the glutamine effects.…”
Section: Discussionmentioning
confidence: 50%